Catalytic activity trends from pure Pd nanoclusters to M@PdPt (M = Co, Ni, and Cu) core-shell nanoclusters for the oxygen reduction reaction: A first-principles analysis. (11th May 2020) - Cruz-Martínez, H.; Tellez-Cruz, M.M.; Solorza-Feria, O.; Calaminici, P.; Medina, D.I.
Abstract: The trends of the catalytic activity toward the oxygen reaction reduction (ORR) from Pd44 nanoclusters to M6 @Pd30 Pt8 (M = Co, Ni, and Cu) core-shell nanoclusters was investigated using auxiliary density functional theory. The adsorption energies of O and OH were computed as predictors of the catalytic activity toward the ORR and the following tendency of the electrocatalytic activity was computed: Pt44 ≈ M6 @Pd30 Pt8 > M6 @Pd38 > Pd44 . In addition, the adsorption of O2 on the Ni6 @Pd30 Pt8 and Pt44 nanoclusters were investigated, finding an elongation of the O–O bond length when O2 is adsorbed on the Ni6 @Pd30 Pt8 and Pt44 nanoclusters, suggesting that the O2 is activated. Finally, the stabilities of the M6 @Pd38 and M6 @Pd30 Pt8 core-shell nanoclusters were analyzed both in vacuum and in oxidative environment. From the calculated segregation energies for the bimetallic and trimetallic nanoclusters in vacuum, it can be clearly observed that the M atoms prefer to be in the center of the M6 @Pd38 and M6 @Pd30 Pt8 nanoclusters. Nevertheless, it is observed that the segregation energies of M atoms for the M6 @Pd38 nanoclusters with an oxidizing environment tend to decrease compared with their M6 @Pd38 nanoclusters counterparts in vacuum, which suggests that in an oxidative environment, M atoms may tend to segregate to the surface of the M6 @Pd38 nanoclusters. Highlights: The O and OH adsorption energies were computed as predictors of the catalytic activity for the ORR. The stabilities of the M6 @Pd38 and M6 @Pd30 Pt8 core-shell nanoclusters were investigated through segregation energy. The M6 @Pd38 core-shell nanoclusters present lower O adsorption energy with respect to the pure Pd44 nanocluster. The following tendency of the ORR catalytic activity was found: Pt44 ≈ M6 @Pd30 Pt8 > M6 @Pd38 > Pd44 . The formation of core-shell structures is favored in the M6 @Pd38 and M6 @Pd30 Pt8 (M = Co, Ni, and Cu) systems.